A new species of Pantelodes (Lepidoptera: Bombycoidea: Apatelodidae) from Southern Bahia, Brazil - Orlandin, Elton; Carneiro, Eduardo (Zootaxa, 2021)
A recent taxonomic study revealed that specimens so far identified as Apatelodes satellitia (Walker, 1855) are in fact representatives of a complex of cryptic species. A new genus was established to hold this complex of species, namely Pantelodes Herbin, 2017. Here we describe a new species of Pantelodes from Southern Bahia Atlantic Forest based on morphological and molecular characters. Pantelodes camacana Orlandin & Carneiro sp. nov. is compared with other Pantelodes species and their phylogenetic relationships are discussed.